Assessment of greenhouse gas emissions from agricultural sources in order to plan for needs of low carbon economy at local level in Poland. Issue 2 (3rd July 2018) - Wiśniewski, Paweł; Kistowski, Mariusz
Abstract: Agriculture is often not included in the baseline greenhouse gas (GHG) emission inventories created for local low carbon economy plans in Poland and other European countries. We therefore estimate the size of the carbon footprint from agricultural sources and indicate the share of agriculture in the total GHG emissions in selected Polish communes (LAU level 2). We propose a solution whereby local government units can estimate their carbon footprint independently and monitor the impact of actions taken to reduce emissions. The value of the carbon footprint from agriculture in the selected communes varies from .5 to 46.5 thousand Mg CO2 eq/year, with a mean value of 12.6 thousand Mg CO2 eq/year and a standard deviation of 11.4 thousand Mg CO2 eq/year. Per capita, these values range from 10 kg CO2 eq/year to 8.4 Mg CO2 eq/year, with a mean of 1.1 Mg CO2 eq/year and a standard deviation of 1.5 Mg CO2 eq/year. In all communes, the contribution of agriculture to total emissions is at an average of 14% (values range from .2 to 57.4%). The obtained results confirm the appropriateness of including emissions from the agricultural sector and other related sources in low carbon economy plans.